The Impact of Dialogic Approach on ESP University Students’ Speaking Anxiety and Emotional Well-being - Insaf Khoudri; Umar Fauzan (Indonesian Journal of EFL and Linguistics, 2026)
The aim of this study is to investigate the effectiveness of the dialogic teaching approach in enhancing the emotional well-being and reducing the speaking anxiety of EFL university learners of English for Specific Purposes (ESP). To achieve the objectives of this study, the study was conducted on two groups of undergraduate students from the Department of Management Technique at the High School of Technology in Meknes, Morocco. To collect data, a quasi-experimental research design was adopted, combining a non-equivalent group design with a pretest and a posttest design. To analyze data, SPSS was used to employ two tests. A t-test for within-group comparisons before and after the intervention, and an independent sample test for between-group comparisons pre- and post-intervention. Drawing on the findings, the dialogic approach was successful in enhancing ESP learners’ speaking skills, reducing their speaking anxiety, and improving their emotional well-being, in contrast to the control group, which continued with traditional lectures and did not receive any intervention. Hence, the study implies that developing students’ public speaking skills and using interactive teaching methods becomes a requirement to alleviate students’ speaking anxiety while increasing students’ emotional well-being